SYNCHRONIZATION OF CATTLE USING HORMONAL PREPARATIONS ESTROPHAN, SURFAGON, AND E-SELENIUM - D. Gabdullin; A. Mukataev; D. Zainettinova; A. Kozhayeva; K. Oryntaev; B. Satybaev (Animal Health and Biosafety, 2026)
This study aimed to improve the reproductive performance of Hereford cattle through the application of hormonal synchronization protocols, with particular emphasis on estrus induction and the efficiency of artificial insemination (AI). The research was conducted at the "Masakbay" LLC farm located in Pavlodar region, Kazakhstan, during the period from 2018 to 2020. A total of 132 clinically healthy cows aged between 2.5 and 5 years, with live body weights ranging from 350 to 600 kg, were included in the experiment. Comprehensive reproductive assessments were carried out using standard veterinary diagnostic methods, including rectal palpation, ultrasonography, and hormonal profiling. These approaches allowed accurate monitoring of ovarian activity, follicular development, and reproductive status throughout the study period. The hormonal synchronization protocol involved the use of Estrophan (a prostaglandin analogue), Surfagon (a GnRH analogue), and E-Selenium to support metabolic and reproductive functions. The application of these препаратов resulted in a significant improvement in estrus synchronization and reproductive outcomes. In the first experimental group, 76% of cows successfully conceived, while in the second group the pregnancy rate reached 81.25% within 28 days following treatment. Notably, the second group demonstrated a more rapid and synchronized estrus response, with 53.2% of animals exhibiting estrus within three days after Surfagon administration. This indicates a higher efficiency of the protocol when precise timing and hormonal combinations are optimized. Gynecological examinations revealed a generally good reproductive health status among the animals. Only five cases of follicular cysts were detected, all of which were successfully treated without long-term reproductive consequences. Overall, the findings confirm that hormonal synchronization combined with artificial insemination is an effective strategy for enhancing reproductive efficiency in Hereford cattle. Key factors influencing success include semen quality, proper animal management, nutritional status, and accurate timing of insemination procedures.